ANALISIS STRATEGI PENGEMBANGAN SEKTOR INFORMAL DI KOTA MEDAN - Togi naomi Marito Siregar; Paidi Hidayat (Ekonomi dan Keuangan, 2014)
This study aims to assess the internal factors and external factors determine the development of the informal sector and development strategy informal sector in Medan. This study uses primary data collected directly from the informal sector workers in Medan and analyzed using quantitative SWOT analysis. Internal factors that influence the development of the informal sector in the city of Medan is: Expertise (HR), Working Capital, Labor, Technology, Availability of Raw Materials, Raw Materials Price, Facilities and Infrastructure, Work Experience, and Promotion. As for the external factors that influence the development of the informal sector in the city of Medan is: Rental Costs, Training, Opportunity, soft Lending, Loans, Partnership, Competition, Economic Conditions are not stable, Law, Policy Development, and the existence of the Formal Sector. Based on the SWOT analysis of the informal sector, development strategy in Medan is developing the informal sector by providing loans to actors in the informal sector activities, provide additional capital to develop the informal sector, providing raw materials through the existence of a partnership.Keyword: Informal Sector, Strategy Development, SWOT, Internal Factors, External Factors